Shared responsibility: school nurses' experience of collaborating in school‐based interprofessional teams. Issue 2 (21st July 2016) - Reuterswärd, Marina; Hylander, Ingrid
Abstract : Background: The Swedish Education Act (2011) mandated a new combination of services to boost students' physical health, their mental health and special education through interprofessional pupil health and well‐being (PH) teams. For Swedish school nurses, providing these services presents new challenges. Aim: To describe how Swedish school nurses experience their work and collaboration within the interprofessional PH teams. Methods: Twenty‐five school nurses (SNs) were interviewed in five focus groups. Content analysis was used to examine the data and to explore SNs' workplace characteristics by using the components of the sense of coherence (SOC) framework. Results: SNs' experiences of work and collaboration within PH teams can be described using three domains: the expectations of others regarding SNs' roles, SNs' contributions to pupils' health and well‐being, and collaboration among SNs within PH teams. The results indicate a discrepancy between SNs' own experiences of their contribution and their experiences of other professionals' expectations regarding those contributions. Some duties were perceived as expected, comprehensible, manageable and meaningful, while other duties – though expected – were perceived as less meaningful, taking time away from school‐related matters. Other duties that were not explicitly expected – promoting general health and creating safety zones for pupils, teachers and parents, for example – were nonetheless perceived as meaningful. Collaboration within PH teams was considered meaningful, comprehensible and manageable only if the objectives of the team meetings were clear, if other professionals were available and if professional roles on the team were clearly communicated. Conclusion: The SNs reported a lack of clarity regarding their role in PH and its implementation in schools, indicating that professionals in PH teams need to discuss collaboration so as to find their niche given the new conditions. SOC theory emerged as a useful framework for discussing concrete work‐related factors in the school environment.